2002
DOI: 10.1037/0096-1523.28.5.1019
|View full text |Cite
|
Sign up to set email alerts
|

Why do non-color words interfere with color naming?

Abstract: In the non-color-word Stroop task, university students' response latencies were longer for low-frequency than for higher frequency target words. Visual identity primes facilitated color naming in groups reading the prime silently or processing it semantically (Experiment 1) but did not when participants generated a rhyme of the prime (Experiment 3). With auditory identity primes, generating an associate or a rhyme of the prime produced interference (Experiments 2 and 3). Color-naming latencies were longer for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 113 publications
9
118
3
2
Order By: Relevance
“…No valence effect was found for response type or for response latency. This result is in line with other studies using different paradigms showing that when controlling for factors such as arousal or origin of emotionally charged materials, the valence effects disappear (Burt 2002;Imbir and Jarymowicz 2013;Siegle et al 2002;Williams et al 1996). Without care in controlling for those factors, one may compare, for example, negatively valenced and highly arousing stimuli with positively valenced and low arousing ones, and arrive at a mistaken conclusion about the impact of valence.…”
Section: Discussioncontrasting
confidence: 32%
“…No valence effect was found for response type or for response latency. This result is in line with other studies using different paradigms showing that when controlling for factors such as arousal or origin of emotionally charged materials, the valence effects disappear (Burt 2002;Imbir and Jarymowicz 2013;Siegle et al 2002;Williams et al 1996). Without care in controlling for those factors, one may compare, for example, negatively valenced and highly arousing stimuli with positively valenced and low arousing ones, and arrive at a mistaken conclusion about the impact of valence.…”
Section: Discussioncontrasting
confidence: 32%
“…The kind of suppression that we suggest is measured in our experiments deals with later stages of processing, where phonological codes are constructed (see Burt, 2002, for a similar proposal regarding the modulation of phonological processes in the color Stroop task). Thus, tasks such as word naming and phoneme detection but not necessarily lexical decision are affected.…”
Section: Learned Modulation Of Component Processesmentioning
confidence: 99%
“…Conflict is particularly strong if the word refers to a color, but substantial conflict also occurs even when words do not refer to colors (Burt, 2002;Klein, 1964;Monsell, Taylor, & Murphy, 2001). We assume that to resolve such task competition, some aspect or aspects of the nonselected task must be suppressed, particularly if that task is the more habitual or dominant one.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As Kinoshita et al also showed, reading the word (and thus having a task conflict) is more likely to occur when the modality of colour response also involves phonology (i.e., vocal responses); as this interference is driven by pronounceability, it increases the more there are letters in the word. In addition, frequency manipulations (e.g., Burt, 2002;Monsell et al, 2001) have shown a (not always reliable) trend, whereby words seen often in the language are colour-named faster than words seen less often. Thus, subtle (uncontrolled) differences in the linguistic make-up of the words could be behind the emotional Stroop.…”
Section: Introductionmentioning
confidence: 99%